SLC7A11-ROS/αKG-AMPK axis regulates liver inflammation through mitophagy and impairs liver fibrosis and NASH progression - Tingting Lv; Xiude Fan; Chang He; Suwei Zhu; Xiaofeng Xiong; Wei Yan; Mei Liu; Hongwei Xu; Ruihua Shi; Qin He (Redox Biology, 2024)
The changes of inflammation and metabolism are two features in nonalcoholic steatohepatitis (NASH). However, how they interact to regulate NASH progression remains largely unknown. Our works have demonstrated the importance of solute carrier family 7 member 11 (SLC7A11) in inflammation and metabolism. Nevertheless, whether SLC7A11 regulates NASH progression through mediating inflammation and metabolism is unclear. In this study, we found that SLC7A11 expression was increased in liver samples from patients with NASH. Upregulated SLC7A11 level was also detected in two murine NASH models. Functional studies showed that SLC7A11 knockdown or knockout had augmented steatohepatitis with suppression of inflammatory markers in mice. However, overexpression of SLC7A11 dramatically alleviated diet-induced NASH pathogenesis. Mechanically, SLC7A11 decreased reactive oxygen species (ROS) level and promoted α-ketoglutarate (αKG)/prolyl hydroxylase (PHD) activity, which activated AMPK pathway. Furthermore, SLC7A11 impaired expression of NLRP3 inflammasome components through AMPK-mitophagy axis. IL-1β release through NLRP3 inflammasome recruited myeloid cells and promoted hepatic stellate cells (HSCs) activation, which contributed to the progression of liver injury and fibrosis. Anti-IL-1β and anakinra might attenuate the hepatic inflammatory response evoked by SLC7A11 knockdown. Moreover, the upregulation of SLC7A11 in NASH was contributed by lipid overload-induced JNK-c-Jun pathway. In conclusions, SLC7A11 acts as a protective factor in controlling the development of NASH. Upregulation of SLC7A11 is protective by regulating oxidation, αKG and energy metabolism, decreasing inflammation and fibrosis.